Draft Annual Plan 2006-2007 Government of Mizoram - Planning Commission (Planning Commission, 2006)
Mizoram is situated in the southern-most corner of the North Eastern Region and is bounded on the north by the States of Assam and Manipur, on the east and south by Chin Hills of Myanmar and on the west by Chittagong Hill Tracts of Bangladesh and the State of Tripura. It covers an area of 21,087 Sq. Km. It has an International Boundary of 404 Km. with Myanmar and 318 Km. with Bangladesh.
Planning and Programme Implementation Department, Government of Mizoram